Evaluation of some quality parameters of cassava starch and soy protein isolate matrices during deep fat frying in soybean oil. Issue 2 (19th December 2018) - Omidiran, Adebukola T.; Sobukola, Olajide P.; Sanni, Silifat A.; Sanni, Lateef O.; Adebowale, Abdulrasaq A.; Shajobi, Adebola O.; Kulakow, Peter
Abstract: Snack industry is recently focused on the production of snacks with minimal oil content and enhanced quality attributes which prompted the need to study the changes in snack matrices produced from cassava starch processed from three varieties of cassava roots (TMS‐950289, TME‐419, and TMS‐30572) and soy protein isolate blends fried in soybean oil. Effect of frying temperature (170–180°C), frying time (2–4 min), soy protein isolate inclusion level (5%–15%) on proximate composition, color changes, expansion, texture, and sensory attributes of the snacks was investigated. Optimization of process variables was carried out based on a factorial design (2 level by 3 factor) in the Design Expert version 6.0.8, and models were generated showing the relationship between the independent variables and the responses. The desired goal for each constraint (processing conditions) was kept within 170–180°C for 2–4 min, while all responses, except chewiness, expansion, yellowness, and protein, were set at minimum. Evaluation of sensory attributes of the optimized sample was carried out to determine its level of desirability. The optimized frying conditions for matrices produced from starches of TMS‐950289 are 170°C/4 min/5% SPI with desirability value of 0.507; from TME‐419 are 180°C/2 min/5% SPI with desirability value of 0.475 while for those from TMS‐30572 are 170°C/4 min/15% SPI with desirability value of 0.459. At higher SPI level, the protein content was high at 170°C. At 4 min frying time for all the varieties, the moisture content reduces. The most desired optimized fried snack produced from starch of TMS‐30572 (containing 15% SPI) had higher crispness and lower oil content than other optimized fried snacks. Abstract : Consumer trends toward healthier and low fat products have had a significant impact on the snack industry; the objective of this work is to evaluate quality attributes of snacks produced from cassava starch produced from three varieties of cassava roots (TMS‐950289, TME‐419, and TMS‐30572) and soy protein isolate blends fried in soybean oil. Parameters evaluated include proximate analysis, texture analysis, expansion, and color changes. Effect of frying temperature (170–180°C), frying time (2–4 min), soy protein isolate inclusion level (5%–15%) on some quality attributes of fried snack using cassava starch and soy protein isolate was investigated. Data were analyzed using Design Expert version 6.0.8, significant effect of the independent variables on the responses at 5% level was determined using Analysis of Variance (ANOVA), and models were generated showing the relationship between the independent variable and the responses. Numerical optimization technique was used for simultaneous optimization of the multiple responses, and the desired goal for each processing parameter and response was chosen. All the processing parameters were kept within range while all responses, except chewiness, expansion, yellowness, and protein, were set at minimum. Based on optimization, the frying temperature of 170°C, frying time of 4 min, and 5% SPI with desirability value of 0.507 were selected for TMS‐950289, the frying temperature of 180°C, frying time of 2 min, and 5% SPI with desirability value of 0.475 were selected for TME‐419, and the frying temperature of 170°C, frying time of 4 min, and 15% SPI with desirability value of 0.459 were selected for TMS‐30572. Sensory evaluation of the optimized sample to determine its level of desirability was carried out. It was observed that the higher the SPI, the higher the protein content at low temperature. At high frying time, the moisture content reduces. The most desired optimized fried snack produced from starch of TMS‐30572 (containing 15% SPI) had high crispness, and lower oil content than other optimized fried snacks.